DISTRACTION OSTEOGENESIS IN SEGMENTAL BONE DEFECTS IN TIBIA BY MONOAXIAL EXTERNAL FIXATOR - Shabir, Mohammad; Arif, Mohammad; Satar, Abdul; Inam, Mohammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the results of segmental bone transport using monoaxial external fixator in patients with non union of the tibia with segmental bone loss. Material and Methods: This descriptive study was carried out at orthopedic unit of Hayatabad Medical complex Peshawar from July 2004 to January 2007 with 32 patients of tibial non union with segmental bone loss. Locally made "Naseer-Awais" uniplanner external fixator was applied and osteotomy performed. Distraction started at tenth post operative day. Patients were followed fortnightly. Check radiographs were taken on every visit. At the end of consolidation phase fixtor was removed. Results were assessed using Association for the Study and Application of the Method of ILIZAROV (ASAMI) scoring system. Results: Out of 32 patients 29 were male and 3 were female. Eighteen patients had road traffic accidents, 10 fire arm injuries and 4 bomb blast injuries. Average length of bone transport was 7cm. Average duration of fixator was 8 months and average follow up was 25 months. Eight(25%) patients had some additional procedure in form of fibular osteotomy, fasciocutaneous flap and bone grafting. Twentyeight( 87.5%) patients had pin tract infection. Repositioning of pins was done in 18(56.25%) patients. External fixator was changed in 10(31.25%) patients. Four patients developed mal-alignment which required fixator resetting. Four(12.5%) patients had re-osteotomy. Five(15.62%) patients developed persistent equinus deformity Nine(28.12%) patients had to modify their profession. Conclusion: Distraction osteogenesis can be achieved with locally made Naseer Awais fixator in non union of tibia with segmental bone loss.